Pulmonary artery aneurysms in Behçet disease - Shi-Min Yuan (Jornal Vascular Brasileiro, 2014)
Pulmonary artery aneurysms (PAAs) are the most common type of pulmonary involvement in Behçet's disease. However, the relationships between clinical features and prognosis have not been sufficiently evaluated. This article describes the results of a comprehensive review, revealing that PAAs have a predilection for hemoptysis manifestations, increased dimensions, right lower lobar location, multiplicity and concurrent intramural thrombus formation. Surgical intervention was needed in one third of patients. Patients with massive hemoptysis and PAA rupture warranted emergency operations. Conservatively treated patients were prone to PAA progression; interventional embolization was associated with higher risks of recurrence and reintervention for PAAs; and surgically treated patients exhibited the highest mortality rates. In conclusion, PAAs in Behçet's disease are characterized by a predilection for hemoptysis manifestations, right lower lobar location, multiplicity, and concurrent intramural thrombus formation. Both the condition itself and the surgical operations it warrants are linked with high mortality due to PAA hemorrhage.